Communication Research on Energy Efficiency in India : Communication Needs Assessment and Stakeholder Mapping - Worley, Heather; Sarkar, Ashok; Mukhi, Neha; Padmanaban, Padu S.; Kumar, Amit; Nair, Jayakrishnan; Soni, Manish (World Bank, Washington, DC, 2017)
India is the world’s third largest consumer of energy. It is widely acknowledged that the role of energy efficiency (EE) in reducing India’s carbon dioxide emissions and improving energy security is critical. Achieving the overarching goal of increasing EE in South Asia would be enabled by a well-planned, professionally executed public communication strategy and outreach program with clear audience segmentation. As the first step towards implementing a strategic communication program, the World Bank commissioned an analysis of EE-related. communications in India targeted towards various stakeholders and energy consumers. This communication analysis, including mapping of key stakeholders in the Indian EE communications landscape, is part of the World Bank’s implemented program titled ‘scaling up the demand side energy efficiency business line in South Asia’, and will inform a communications strategy that aims to increase awareness and foster an enabling policy and business environment for EE in India. The study aims to understand the attitudes of the policymakers and nodal agencies, EE implementers, and consumers (industries and general public from various energy consuming sectors) about EE, and gauge the various stakeholders’ informational needs and preferred channels of information on EE issues. In order to influence more energy efficient behaviors in India, there is a need to examine what has worked in motivating new behaviors, and what has not worked and why. The research also aims to map various categories of stakeholders in the EE landscape in India, which have an impact on identifying, developing, designing, and implementing EE improvement activities in all major energy consuming sectors, namely, Industry, Transport, Agriculture, Commercial, and Residential.